Design of Infographic for Children About Indonesia's Endemic Chickens - Fred Areal Petrof; Syakir Syakir (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Low public awareness, particularly among children, poses a significant threat to the conservation of Indonesia’s 31 native chicken breeds, which are increasingly at risk due to habitat loss, illegal hunting, and overexploitation. To address this challenge, this study was conducted to design an educational infographic that introduces these endemic chicken species to children by combining scientific accuracy with creative visual communication. The research followed a three-stage methodology, beginning with pre-production, where data were collected from credible sources such as scientific journals, government publications, and academic literature, followed by the organization of information into a visual narrative supported by layout planning, color selection, typography, and illustration style. The production stage translated these concepts into digital media through the creation of child-friendly illustrations in Clip Studio Paint, layout composition in Canva, and integration of supporting graphics to ensure cohesiveness and clarity. Post-production focused on refinement, readability, and factual validation to ensure that the infographic was both accurate and engaging for the target age group. The final design proved effective in simplifying complex biodiversity knowledge, enhancing children’s comprehension, and fostering early awareness of conservation while also promoting pride in Indonesia’s cultural and biological heritage. These results demonstrate the potential of infographic media as a valuable educational tool for biodiversity conservation and environmental stewardship among younger generations.